IMPLEMENTASI MANAJEMEN TALENTA APARATUR SIPIL NEGARA: STUDI KASUS KECAMATAN JATINANGOR - Subhan Saladin; Gloria Stevanie Nauli Sianipar; Ziofari Baldi Amanta; Sahrul Romdoni; Divio Muhamad Julian; Yayan Nuryanto (CV. Denasya Smart Publisher, 2026)
Talent management within the Indonesian Civil Service (ASN/ASN) constitutes a crucial instrument of bureaucratic reform aimed at enhancing the quality and professionalism of government personnel. In the context of local government administration, talent management encompasses not only training and competency development but also recruitment, placement, performance evaluation, and the distribution of personnel according to organizational needs. This study aims to analyze the impact of talent management on the quality of government personnel in Indonesia through a case study of Jatinangor District. The research employs a descriptive qualitative approach utilizing literature analysis, observational records, and interviews concerning personnel management practices in Jatinangor District. The findings indicate that the implementation of talent management in Jatinangor District continues to face several challenges, particularly namely regarding the limited authority of the district government in ASN recruitment, which remains under the jurisdiction of the Regional Civil Service and Human Resource Development Agency (BKPSDM) and local government authorities, the shortage of ASN personnel, the mismatch between employee placement and competency backgrounds, and restricted access to training opportunities. Nevertheless, adaptive measures have been undertaken, including self-directed learning initiatives, training programs organized by BKPSDM in collaboration with the National Institute of Public Administration (LAN), the Ministry of Home Affairs, and academic institutions, monthly performance evaluations based on indicators established by BKPSDM, and internal strategies such as workforce planning through staffing requirement matrices and the direct involvement of section heads in technical tasks. This study concludes that talent management significantly influences the quality of government personnel; however, its effectiveness largely depends on the consistent implementation of the merit system, appropriate employee placement, adequate training support, and sufficient numbers of ASN personnel.